Is your Session Border Controller providing a false sense of security?. Issue 1 (January 2017) - German, Paul
Abstract : Organisations have latched on to the need to secure SIP trunking solutions by implementing a Session Border Controller (SBC). The problem is that the vast majority of SBCs are considered not just one-off investments but also one-off deployments. Yet from denial of service attacks to toll fraud, SIP trunking is not only inherently vulnerable, that vulnerability continues to change and escalate. Few companies would fail to update anti-virus software, so why assume the SBC can protect against changing threats without similar routine updates? The fact is that in their current guise, most SBCs actually leave organisations with a false sense of security.